DEVELOPMENT OF INTERACTIVE MATHEMATICS LEARNING MULTIMEDIA BASED ON SCRATCH USING THE 4D MODEL - Sugeng Sungkono; Al Jupri; Eyus Sudihartinih (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study is motivated by students’ difficulties in understanding applied algebra, particularly when solving contextual problems, as well as the limited availability of interactive digital learning resources for applied algebra learning. Therefore, this study aims to develop and evaluate the validity, usability, and user acceptance of a Scratch-based learning medium for applied algebra using the 4D development model. The research followed the Define, Design, Develop, and Disseminate stages. The development process involved needs analysis, prototype design, and implementation through Scratch, integrating contextual tasks, visual representations, and game-based activities within a single learning environment. Validation was conducted by one mathematics education expert and two experts in educational media and ICT-based learning, while usability and user acceptance were examined through a User Acceptance Test (UAT) involving 18 prospective mathematics teachers. Data were collected using validation sheets and a UAT questionnaire and analyzed using Aiken’s V coefficient and percentage-based descriptive statistics. The findings revealed a high level of validity with an average Aiken’s V value of 0.85 and positive evaluations regarding usability and user acceptance, reflected in an average UAT score of 87.50%. In addition, Dr. Scratch evaluation produced a score of 20 out of 21, placing the project in the Master category. Future studies should involve junior high school students and evaluate the effectiveness of the media in classroom settings. Penelitian ini dilatarbelakangi oleh kesulitan siswa dalam memahami materi aplikasi aljabar, khususnya dalam menyelesaikan masalah kontekstual, serta terbatasnya ketersediaan sumber belajar digital interaktif pada pembelajaran aplikasi aljabar. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan dan mengevaluasi validitas, usability, dan penerimaan pengguna terhadap media pembelajaran berbasis Scratch pada materi aplikasi aljabar menggunakan model pengembangan 4D. Penelitian ini dilaksanakan melalui empat tahap, yaitu Define, Design, Develop, dan Disseminate. Proses pengembangan meliputi analisis kebutuhan, perancangan prototipe, dan implementasi media menggunakan Scratch yang mengintegrasikan tugas kontekstual, representasi visual, dan aktivitas berbasis permainan dalam satu lingkungan pembelajaran. Validasi dilakukan oleh satu ahli pendidikan matematika dan dua ahli media pembelajaran serta pembelajaran berbasis TIK, sedangkan usability dan penerimaan pengguna dievaluasi melalui User Acceptance Test (UAT) yang melibatkan 18 calon guru matematika. Data dikumpulkan menggunakan lembar validasi dan angket UAT, kemudian dianalisis menggunakan koefisien Aiken’s V dan statistik deskriptif berbasis persentase. Hasil penelitian menunjukkan tingkat validitas yang tinggi dengan nilai rata-rata Aiken’s V sebesar 0,85 serta penilaian positif terhadap usability dan penerimaan pengguna yang ditunjukkan oleh skor rata-rata UAT sebesar 87,50%. Selain itu, evaluasi menggunakan Dr. Scratch menghasilkan skor 20 dari 21 sehingga proyek yang dikembangkan termasuk dalam kategori Master. Penelitian selanjutnya perlu melibatkan siswa SMP sebagai pengguna sasaran serta menguji efektivitas media dalam situasi pembelajaran yang sebenarnya.